The N'Gustro affair - Manchette, Jean-Patrick, 1942-1995 (New York Review Books classics., 2021)
"Mean, arrogant, naïve, sadistic on occasion, the young Henri Butron records his life story on tape just before death catches up with him. A death passed off as a suicide by his killers, French secret service agents who need to hush up their role-and Butron's-in the kidnapping, torture, and murder of a leading opposition leader from a third-world African nation in the throes of postcolonial civil war. The N'Gustro Affair is a thinly veiled retelling of the 1965 abduction and killing of Mehdi Ben Barka, a radical opponent of King Hassan II of Morocco. But this is merely the backdrop to Jean-Patrick Manchette's first-person portrait (with shades of Jim Thompson's The Killer inside Me) of a man who lacks the insight to see himself for what he is: a wannabe nihilist too weak to be even a full-bore fascist"--